Некоторые аспекты проявления этнической идентичности в диаспоре (Էթնիկական ինքնությունը որպես սփյուռքի ձևավորման և պահպանման գործոն) - Ջանգոզյան Ստելլա (YSU Journal of International Affairs, 2014)
The article deals with the topical problem of formation of ethnic identity and its manifestation in the communities of Diaspora. The issue of correlation of identity and social consciousness is explained. Distinctive features explaining ethnic identity in the process of social-political problem solving in Diaspora are disclosed by using the propositions of different paradigms.